2016
DOI: 10.1097/mpg.0000000000001006
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Incontinence in Adolescents Is Associated With Child Abuse, Somatization, and Poor Health‐related Quality of Life

Abstract: There is a significant association between FI and physical, sexual, and emotional abuse. They also have a higher somatization score and a poor HRQoL score in physical, emotional, social, and school functioning domains compared with those without FI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 25 publications
2
40
1
Order By: Relevance
“…Somatic symptoms are an integral part of functional gastrointestinal disorders. In previous studies, we have shown that children with constipation and fecal incontinence do have a higher number of somatic symptoms and higher total somatization scores . Similar to these findings, adolescents with AP also were suffering from a large number of somatic symptoms.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Somatic symptoms are an integral part of functional gastrointestinal disorders. In previous studies, we have shown that children with constipation and fecal incontinence do have a higher number of somatic symptoms and higher total somatization scores . Similar to these findings, adolescents with AP also were suffering from a large number of somatic symptoms.…”
Section: Discussionsupporting
confidence: 83%
“…In previous studies, we have shown that children with constipation and fecal incontinence do have a higher number of somatic symptoms and higher total somatization scores. 25,26 Similar to these findings, adolescents with AP also were suffering from a large number of somatic symptoms. In addition, the total somatization score of these adolescents with AP was significantly higher than the controls.…”
Section: Hrqol Of Adolescentssupporting
confidence: 71%
See 2 more Smart Citations
“…This study showed a linear relationship between the number of types of maltreatment and their self-reported QoL. Another crosssectional study examined the relationship between fecal incontinence and self-reported QoL in abused and nonabused adolescents aged 13-18 years (Rajindrajith et al 2016). However, although the prevalence of abuse was higher among adolescents with fecal incontinence, and adolescents with fecal incontinence had lower QoL scores, the study did not report on the association between these two independent variables, i.e.…”
mentioning
confidence: 76%